Analysis of Career Planning and Development of Education Profession Personnel in the Indonesian Navy - Pribadhi, Burhananda Inggil; Liestiawati, Fibria Indriati Dwi (Journal of Governance, 2025)
This research focuses on the study of career planning and development. The object of study is career planning and development for education profession personnel in the Indonesian Navy, using Edgar Schein's Career Anchor Theory to describe a set of self-perceived factors, namely talents-based (talents/competencies), needs-based (needs/motivation), and value-based (values). This study analyzes and describes career planning and development for education profession personnel adopted and implemented within the Indonesian Navy. Career planning and development are crucial aspects in building high-quality human resources, particularly for personnel working in the field of education. The importance of career planning and development in organizations is the top reason for conducting this research. The approach applied in this study is a quantitative positivist approach presented in a descriptive narrative. The results of this study found that career planning and development for education profession personnel in the Indonesian Navy is not optimal yet, and there are no specific and detailed regulations regarding career paths for education profession personnel. Regarding support from leadership, a fair and clear reward system, accessibility to training and further education programs, a strong sense of responsibility toward the role and responsibilities as educators, and organizational culture, these are the factors and barriers influencing career planning and development for education profession personnel within the Indonesian Navy, as identified in this study.